Equation for total body water based on Watson's formula according to abdominal perimeter and age - Guevara-Tirado, Alberto (2024)
Objective: To develop a simplified anthropometric equation of total body water based on abdominal circumference and age based on Watson's formula. Material and methods: Analytical and cross-sectional study, based on data from the 2022 national demographic health survey (population=32,066). The variables were: total body water, age, sex, abdominal perimeter. Neural networks (multilayer perceptron), multiple linear regression, and Spearman correlation were used to compare the results with the 2021 survey population (population=31,966). Results: The multilayer perceptron had a relative error of 0.17 and 0.12 in women and men, respectively. The regression equation in women was: 8.083 + (0.308*abdominal circumference) + (-0.084*age). In men: 12.132 + (0.338*abdominal circumference) + (-0.166*age). The correlation of both equations was compared with a control group (ENDES-2021), finding very strong correlations in men (Rho=0.821) and women (Rho=0.816), similar to those of the main study (ENDES-2022) that had correlations of 0.897 and 0.845 in men and women, respectively. Conclusions: The equation to determine total body water based on abdominal perimeter and age is highly close to Watson's original formula. As it does not require a scale, stadiometer, and is a more simplified equation, it could be applicable to large population groups as a screening instrument.